Social Ecological Resilience System of Ambon Island Protected Forest, Maluku Province, Indonesia (Jurnal Penelitian Kehutanan Wallacea, 2024)
Humans and nature cannot be separated because both have a close relationship as an ecosystem. The purpose of this study was to determine: 1) the level of social and ecological resilience; 2) Scenarios on ecological and social factors for the sustainability of protected forests. The research method uses survey methods and data analysis uses qualitative-verification analysis based on the results of the calculation of the resilience index and the phase of the socio-ecological system. The results showed that the level of social and economic resilience was partially or simultaneously at the level of resilience with their respective indexes: social: 0.6944); ecology: 0.8148 and socio-ecology 0.7460. The exploitation phase (growth) leads to the conservation phase. The results of the scene show that both of them are at a high level of resilience with a resilience index of 0.8889 (high resilience) and a reorganization phase. If this phase can be maintained with various management interventions according to its function, it will minimize the level of disturbance to the Mount Sirimau Protection Forest Group.
Keywords: Disruption; change; system